Genetics and Kinetics of Fetal Cell Microchimerism. - Gilley, Stephanie. (2017)
Abstract: During each pregnancy, cells from the fetus travel into the maternal circulation and organs, resulting in the development of life-long microchimerism. It is currently uncertain whether persistent fetal cells have beneficial or harmful effects on maternal health, or whether they have any effect at all. Evidence from multiple laboratories suggests that microchimeric fetal cells contribute to maternal tissue repair after injury. A deeper understanding of their phenotype and postpartum trafficking patterns of fetal cells would permit better understanding of possible mechanisms by which they affect maternal health. The research presented here aimed to close these knowledge gaps. Using a mouse model in which a wild type female is mated to a male homozygous for the Egfp transgene, fetal cells in the maternal organs were easily identified by their green fluorescence using high-speed flow cytometery. Small numbers of fetal cells were flow-sorted from the maternal lung in both syngeneic and allogeneic matings, facilitating discovery-driven gene expression analysis. Multidimensional gene expression microarray analysis of these fetal cells suggests that fetal cells in the murine maternal lung are a mixed population during pregnancy, consisting of trophoblasts, mesenchymal stem cells (MSCs) and cells of the immune system. Further characterization of fetal MSCs and immune cells in the maternal organs was limited by the small number of cells present. These results underscore the challenges of working with these rare cells. Functional significance of these cell types was further explored in two different injury models, contact hypersensitivity and unilateral pneumonectomy. Previous work has shown that the maternal lungs contain the greatest number of fetal cells, and that their levels increase throughout gestation. These findings were augmented through analysis in this dissertation of the natural history of fetal cells in the postpartum maternal lungs and bone marrow. The results showed that fetal cells persist in these organs until at least three months postpartum in healthy female mice. A two-stage decline was observed, with an initial two and a half-week rapid clearance followed by a trend of gradual decrease. Additionally, an increase in the ratio of live to dead cells within the lung over time suggests that these cells may replicate in vivo. In conclusion, in this work we demonstrate that low numbers of fetal cells can be flow-sorted from the maternal organs and reproducible gene expression information can be obtained from them. In syngeneic pregnancy, fetal cells in the maternal lung are primarily trophoblasts, mesenchymal stem cells, and cells of the immune system. In allogeneic pregnancies, fetal cells appear to be less differentiated. We recommend that future mouse studies of fetal cell microchimerism should use allogeneic matings wherever possible, to more closely reflect the heterogeneity found in human reproduction. We also show that fetal cell clearance in postpartum maternal organs is a two-stage process. Future murine injury experiments investigating the potential postpartum effects of fetal cells on maternal tissue repair should start at a minimum of 17-18 days after delivery to be certain that the initial clearance stage has been completed.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Genetics.; Advisor: Diana Bianchi.; Committee: Peter Brodeur, Gordon Huggins, Janis Lem, and Keelin O'Donoghue.; Keywords: Genetics, Medicine, and Developmental biology.